Architects of Buddhist Leisure Socially Disengaged Buddhism in Asia's Museums, Monuments, and Amusement Parks - McDaniel, Justin Thomas (Contemporary Buddhism, 2016)
Buddhism, often described as an austere religion that condemns desire, promotes denial, and idealizes the contemplative life, actually has a thriving leisure culture in Asia. Justin McDaniel looks at the growth of Asia's culture of Buddhist leisure through a study of architects responsible for monuments, museums, amusement parks, and other sites. In conversation with noted theorists of material and visual culture and anthropologists of art, McDaniel argues that such sites highlight the importance of public, leisure, and spectacle culture from a Buddhist perspective and illustrate how "secular" and "religious," "public" and "private," are in many ways false binaries. Provocative and theoretically innovative, Architects of Buddhist Leisure challenges current methodological approaches in religious studies and speaks to a broad audience interested in modern art, architecture, religion, anthropology, and material culture.